MEMBINGKAI PERAN KAUM PRIA DALAM PERTUMBUHAN GEREJA DI LINGKUP GEREJA PENTAKOSTAL - Simanjuntak, Parulian (The Way: Jurnal Teologi dan Kependidikan, 2025)
The history of Christian civilization records that in every movement across generation, the role of men was vital. Unfortunately, facts on the ground show that there are still many men who call themselves believers, who actually do not understand the importance of their existence for the growth of the church. In the context of academic research in Indonesia, especially in the realm of journals, there are still very few articles discussing the contribution of men to church growth. This research aims to frame the role of men in church growth within the Pentecostal church. By using descriptive qualitative methods as well as support from literature studies, it is hoped that this article will be able to provide a strong, sharp and systematic picture regarding the image of men and their position in the church, a description of church growth in the Pentecostal sphere, as well as the role of men in the growth of Pentecostal churches. It is concluded that men will contribute maximally to the growth of churches in the Pentecostal sphere when they are able to play modeling roles, supporting roles, educational roles and mentoring roles well at home, church environment and at work.